Effect of Giving Combinations Petrissage Massage with Kenanga Aromatherapy on the Level of Dysmenorrhea - Hapsari, Bunga Kunti; Kostania, Gita; Argaheni, Niken Bayu; Prihati, Dwi Retna (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2023)
Background: The number of dysmenorrhea in Indonesia is 64,25%. About 54,98% had primary dysmenorrhea, and 9,36% had secondary dysmenorrhea. The continuity of abdominal muscle contraction causes the pain of dysmenorrhea during the menstrual period. A combination of gentle massage and linalool in aromatherapy will stimulate the hypothalamus to produce endorphin hormones to reduce the tension of the uterus’s muscle due to the menstrual.Objective: To know the effect of combining petrissage massage with Cananga aromatherapy for dysmenorrhea in teenage girls at senior high school.Methods: This research used Pre Experimental method with one group pretest-postest approach. The population for this study is 540 people. The sampling technique used a rule of thumb by the number of 30 people of teenage girls at the high school. A parametric test and paired t-test processed the data.Result: After giving intervention was available, 28 respondents (93%) with dysmenorrhea reduced, and 2 respondents (7%) remained dysmenorrhea. The analysis result was obtained with a p = 0,000 (p<0,05), which showed the effect of combining petrissage massage with Cananga aromatherapy for dysmenorrhea.Conclusion: A combination of petrissage massage with Cananga aromatherapy can reduce dysmenorrhea